Dialogue intervention for youth amidst intractable conflict attenuates neural prejudice response and promotes adults' peacemaking. Issue 5 (14th October 2022) - Levy, Jonathan; Influs, Moran; Masalha, Shafiq; Goldstein, Abraham; Feldman, Ruth
Abstract: Humans' dependence on group living has led to the formation of tenacious, often nonconscious negative perceptions of other social groups, a phenomenon termed "intergroup bias" that sustains one of the world's most imminent problem: intergroup conflicts. Adolescents' participation in intergroup conflicts has been continuously on the rise, rendering the need to devise interventions that can mitigate some of their deleterious effects on youth an urgent societal priority. Framed within the Israeli–Palestinian conflict and targeting youth, we implemented a dialogue-enhancing intervention for adolescents (16 to 18 years) reared amidst intractable conflict that builds on social synchrony and the neurobiology of affiliation. Implementing a randomized controlled trial design, before and after the 8-week intervention adolescents underwent magnetoencephalography to assess a neural marker of implicit prejudice and interviewed on their attitudes toward the conflict. Adolescents who received the intervention showed attenuation of the neural prejudice response, as indexed by sustained occipital alpha that was significantly reduced at post-intervention and adopted attitudes of peacemaking. Change in the neural prejudice response predicted attitudes of compromise and support in peacebuilding 7 years later, when young adults can already engage in active civil duties and responsibilities. These results underscore adolescence as a window of opportunity for enhancing inter-group dialogue and demonstrate the long-term associations between the neural evaluation of prejudice and self-reported measures of proclivity for compromise and peace in the context of an intractable century-long conflict.